Effect of Beauregard sweet potato paste supplementation on physicochemical and sensory characteristics of soymilk gelato - Susanti, Siti; Damayanti, Viena Aulia; Legowo, Anang Mohamad; Setiani, Bhakti Etza; Bintoro, Valentinus Priyo; Nuryanto, Nuryanto (Progress in Nutrition, 2025)
Background and aim: Gelato is a frozen dessert that is in demand by many people. Soymilk gelato with the addition of BSP paste is a functional gelato innovation. This study aims to determine effect of variations in BSP paste addition on the physicochemical and hedonic properties of soymilk gelato.Methods: The experimental design used was a CRD with 5 treatments and 4 replications, namely 0%, 7.5%, 15%, 22.5%, and 30% BSP paste. The research method consists of experimental design, research procedures, parameter analysis, and data analysis.Results: The results showed that soymilk gelato with the addition of BSP paste had a significant (p